Seroprevalence study of Toscana virus and viruses belonging to the Sandfly fever Naples antigenic complex in central and southern Italy - Serena Marchi; Claudia M. Trombetta; Otfried Kistner; Emanuele Montomoli (Elsevier, 2017)
Sandfly fever viruses are transmitted by the bite of phlebotomine sandflies; serotypes sandfly fever Naples virus, sandfly fever Sicilian virus and sandfly fever Cyprus virus cause febrile illness, whereas Toscana virus (TOSV) may cause neuroinvasive infections. Although TOSV is an important cause of aseptic meningitis in central and southern Italy, in many cases the infection is asymptomatic, leading to underestimation of the actual spread of the virus. This serosurvey aimed to assess the seroprevalence of TOSV in a random population in Siena (Tuscany, central Italy) in 2003-2004 and 2013-2014 and Bari (Apulia, southern Italy) in 2004 and 2015. 2132 serum samples were tested for the presence of anti-TOSV/SFNV IgG by means of ELISA and IFA commercial tests. Seroprevalence rates were compared in the two cities and over a ten-year period in the same city. Seroprevalence results in the Siena population (22.95% in 2003-2004 vs 26.75% in 2013-2014) confirmed the endemic circulation of TOSV and closely related viruses in central Italy, without major changes over the last decade, while no significant prevalence was observed in Bari (2.90% in 2004 vs 1.85% in 2015). Keywords: Toscana virus, Sandfly, Seroprevalence, Phlebovirus, Italy